A NEW CHAPTER IN ACCOUNTABILITY: TRANSPARENCY AND ANONYMISATION IN THE CROATIAN COURTS - PAULA ŠAMANIĆ MATIJEVIĆ; MARTINA TIČIĆ (Anali Pravnog Fakulteta u Beogradu)
The ongoing digitalisation of judicial systems has intensified the debate over balancing the requirement of transparency and the right to privacy. In Croatia, recent legislative amendments mandate online publication of judgments, which marks a significant step toward ensuring transparency. However, this raises questions about reconciling public access to information with individual privacy protection. This article thus evaluates the implications of these changes, examining their compliance with privacy standards and their impact on judicial practices. It assesses whether current legal provisions adequately balance transparency and privacy, particularly by evaluating the existing anonymisation measures. By situating Croatia’s reforms within a comparative legal context, the study also highlights the challenges and opportunities in implementing the obligation of online publication of judgments. The findings aim to assess whether the current solution represents a balanced approach to achieving transparency in the judiciary while safeguarding privacy rights, and offer recommendations for potential improvements.